2010
DOI: 10.1007/s10805-010-9117-9
|View full text |Cite
|
Sign up to set email alerts
|

What is Ethical About Grade Inflation and Coursework Deflation?

Abstract: Recent research questions the validity of student evaluation of teaching (SET) data to measure teaching and learning. Yet, there is extensive use of this instrument around the world, which arguably contributes to a decline in the rigor of college classes. This performance measurement has lead to both unethical grade inflation and coursework deflation as faculty try to entertain students rather than educating them. These unethical teaching techniques used by many faculties are on the same plane as the unethical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In addition, students sometimes use these evaluations to threaten their instructors by giving those low scores and complaining about their instructors' teaching effectiveness to intimidate and force them to accept late assignments, sloppy work, and all forms of excuses (Shapiro, 2002, cited in Crumbley et al, 2010. Therefore, Crumbley et al (2010) recommend that instructors should be punished for the unethical teaching techniques they use to "cook" their student evaluation scores by inflating grades. Appropriate actions must be taken by administrators against all faculty members who inflate their students' grades or decrease the course materials in order to escape low scores in their student evaluations (Crumbley et al, 2010 shown that student evaluations of their teachers is considered to be the main factor correlated with grade inflation, but the correlation between high grades and high student evaluations remains controversial (Abbott, 2008, p. 33).…”
Section: Characteristics Of Effective Student Evaluations Of Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, students sometimes use these evaluations to threaten their instructors by giving those low scores and complaining about their instructors' teaching effectiveness to intimidate and force them to accept late assignments, sloppy work, and all forms of excuses (Shapiro, 2002, cited in Crumbley et al, 2010. Therefore, Crumbley et al (2010) recommend that instructors should be punished for the unethical teaching techniques they use to "cook" their student evaluation scores by inflating grades. Appropriate actions must be taken by administrators against all faculty members who inflate their students' grades or decrease the course materials in order to escape low scores in their student evaluations (Crumbley et al, 2010 shown that student evaluations of their teachers is considered to be the main factor correlated with grade inflation, but the correlation between high grades and high student evaluations remains controversial (Abbott, 2008, p. 33).…”
Section: Characteristics Of Effective Student Evaluations Of Teachingmentioning
confidence: 99%
“…Therefore, Crumbley et al (2010) recommend that instructors should be punished for the unethical teaching techniques they use to "cook" their student evaluation scores by inflating grades. Appropriate actions must be taken by administrators against all faculty members who inflate their students' grades or decrease the course materials in order to escape low scores in their student evaluations (Crumbley et al, 2010). Student evaluations of teaching forms are usually used for www.ccsenet.org/hes…”
Section: Characteristics Of Effective Student Evaluations Of Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Raveche’s teaching skills were lacking and he could not use other techniques that could inflate student evaluations, such as deflating the course content or examinations (Crumbley and Smith, 2009), he made the rather unorthodox decision to reveal the exams. Because the administrators wanted satisfied students and the students wanted high grades with little effort, he was able to satisfy their goals along with his own by using the examination‐oriented teaching strategy (Bhattacharyya, 2004; Crumbley, Flinn, and Reichelt, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable examination of students and the curriculum. Many critics claim the focus should also be on the ethics and integrity of academe itself (Crumbley, Flinn, and Reichelt, 2010; De Russy, 2003). Yet, research into the role of faculty members and university culture regarding academic conduct is somewhat limited.…”
mentioning
confidence: 99%